Incursions of sea lamprey, Petromyzon marinus, and striped bass, Morone saxatilis, in Labrador waters: Episodic events or evidence of a northward range expansion?. Issue 6 (27th September 2021) - Van Leeuwen, Travis E.; Cote, David; Pretty, Christina; Townley, Joseph; Poole, Rebecca; Dempson, Brian; Bird, Tomas J.; Kippenhuck, Charlene; Morris, Corey
Abstract: We describe observations of sea lamprey ( Petromyzon marinus ) and striped bass ( Morone saxatilis ) incursions into Labrador, Canada. While P. marinus have been periodically observed in similar latitudes, their numbers have conspicuously increased in estuarine environments in 2020. In contrast, M. saxatilis were not observed from Labrador until 2017 but appear to be declining after the initial surge in abundance that peaked in 2018. It remains unclear whether spawning populations of either species exist. Given the potential to negatively affect species of commercial and cultural importance through predation, follow‐up surveys are warranted.